A Study On Service Quality at Open University Malaysia and Its Relationship With Students Satisfaction /Joshua Mariyam Anak Duum and Jamadil Halim Azmi Bazir - Duum, Joshua Mariyam; Azmi Bazir, Jamadil Halim (2014)
The purpose of this study is to determine the level of service quality for student management at Open University Malaysia (OUM), Sarawak Learning Centre, Kuching. At the same time, we also wanted to find out how satisfied the students are with the university and whether students satisfaction are influenced by service quality. To obtain the data for this study, questionnaires were distributed to the students during their tutorial. The questionnaire was developed based on the SERVQUAL model. SERVQUAL is a very popular model in the study of service quality developed by Parasuraman in 1998. The model consists of 22 items grouped according to 5 dimensions namely tangibility, reliability, responsiveness, assurance and empathy with the constructs designed to measure service quality and relationship to overall satisfaction. The data gathered was processed and analysed using the SPSS version 17. We conducted the relevant tests, such as the regression analysis, correlations, and cross tabulations to obtain the mean, median and the descriptive statistics which were used to determine the level of service quality at OUM and students satisfaction. The study results showed that both service quality and students satisfaction at OUM are quite high. And our tests also discovered that there is a positive relationship between students satisfaction and service quality.